(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The Millennium era comes with changes in economy, more regulatory controls, political unrests, digitization, and internet explosion .Its really critical for organizations to offer something unique to customers to earn more business and succeed. With revolution in IT and Technology, the customer expectations are very high and their tastes are changing very rapidly. With the Cloud, Analytical, Mobility and Social media, the consumers have access information. Consumers are looking at products and services with CR to improve their lives.